Азбука плетения - Кузьмина Марина Анатольевна (Легпромбытиздат, 1994)
Экземпляры: КХ (19971105) / Инвентарный номер: 1018981 / Цена: 5400.00 / Сис.шифр: 37.248 / Авт.знак: К 89 / ГРНТИ: 64 / ББК: 37.248